Evaluation of uva camarona (macleania rupestris kunth a.c. smith) propagation with air layering (2013)
Uva camarona (Macleania rupestris Kunth A.C. Smith) belongs to the Ericaceae family and grows in  páramo and subpáramo areas in Colombia, between 2,200 and 3,500 m a.s.l. This plant presents edible  berries that serve as a source of food and small income for local communities. The absence of a  propagation protocol for this species limits its use. This study aimed to evaluate the  effectiveness of asexual propagation of M. rupestris with air layering, using indole-butyric acid  (IBA) as a rooting hormone at different concentrations: 0, 500, 1,000, and 2,000 mg L-1. The  results showed that an exogenous application of IBA accelerated the rooting process in the layered  zone, with a notable emission of first adventitious roots at 60 days from the start of the  experiment. The treatments of 500 and 1,000 mg L-1  IBA had the highest number of roots per layer,  being two to three times higher than those presented in the control. No significant differences were seen in root length between treat- ments. The treatments of 500 and 1,000 mg L-1  IBA showed a  high production for the dry weights of the roots and callus, with a higher weight of callus  compared to root weight. Air layering negatively affected the longitudinal growth of the branches, since their average growth rate was 1.49 cm per month, while the growth of intact branches was 2.78 cm per month. The re- sults suggest that the best concentration for rooting was 1.200 mg L-1  IBA because it had the largest number and dry weight of roots in air-layered M. rupestris.